Qing-Re-Xiao-Zheng-Yi-Qi formula relieves kidney damage and activates mitophagy in diabetic kidney disease - Wu, Qiaoru; Yan, Runze; Yang, Hanwen; Wang, Yixuan; Zhang, Chao; Zhang, Jiale; Cui, Zhaoli; Wang, Yaoxian; Sun, Weiwei (Frontiers in Pharmacology, 2022)
Diabetic kidney disease (DKD) is a potentially devastating disease that significantly increases the risk of cardiovascular diseases and end stage renal disease, different pathogenesis of DKD would ultimately lead to renal fibrosis. Kidney contains a high density of mitochondria, and mitochondrial dysfunction contributes to DKD and renal fibrosis. Mitophagy clears disrupted mitochondria and maintains mitochondrial homeostasis. Qing-Re-Xiao-Zheng-Yi-Qi Formula (QRXZYQF) is an effective prescription based on the “Shen-Luo-Zheng-Jia” theory and has been used in clinical treatment for decades, we have confirmed the efficacy of Qing-Re-Xiao-Zheng-Yi-Qi therapy in DKD through clinical trials. In this study, we investigated the mechanisms of QRXZYQF in the treatment of DKD. We used Vanquish UHPLC™ to analyze the chemical profiling of QRXZYQF freeze-dried powder. We constructed DKD rat models induced by unilateral nephrectomy and high-dose streptozocin injection. We examined blood urea nitrogen, serum creatinine, serum glucose, total cholesterol, triglyceride, serum total protein, albumin，alanine aminotransferase，aspartate aminotransferase and 24h urinary total protein in DKD rats. The renal pathological changes were observed by HE, Masson, PAS stanning and transmission electron microscopy. The levels of fibrosis-related proteins and mitophagy-related proteins were detected by western blot analysis. We also conducted an immunofluorescence co-localization analysis on podocytes to further investigate the effect of QRXZYQF treatment on mitophagy. A total of 27 constituents in QRXZYQF were tentatively identified. We found PINK1/Parkin-mediated mitophagy was inhibited in DKD. QRXZYQF treatment could raise body weight and reduce renal index, reduce proteinuria, improve glycolipid metabolic disorders, ameliorate renal fibrosis, and reduce the expression of Col Ⅳ and TGF-β1 in DKD rats. QRXZYQF treatment could also increase the expression of nephrin, activate mitophagy and protect podocytes in DKD rats and high glucose cultured podocytes.